(untitled) (MAUSAM, 1984)
The surface winds recorded by the ONGC rigs in Arabian Sea during the passage of the time of a severe cyclonic storm in 1976 have been analysed and composite is prepared. The distribution of both the tangential and radial winds exhibits asymmetry with respect to the centre of the cyclone. Of the different formulae tried for the estimation of maximum wind speed from pressure values, Fletcher’s formula is found to give a value close to the recorded maximum wind speed.